Uptake of bilateral-risk-reducing-mastectomy: Prospective analysis of 7195 women at high-risk of breast cancer. (December 2021) - Evans, D.Gareth; Gandhi, Ashu; Wisely, Julie; Clancy, Tara; Woodward, Emma R.; Harvey, James; Highton, Lyndsey; Murphy, John; Barr, Lester; Howell, Sacha J.; Lalloo, Fiona; Harkness, Elaine F.; et al.
Abstract: Background: Bilateral-Risk-Reducing-Mastectomy-(BRRM) is well described in BRCA1/2 pathogenic variant carriers. However, little is known about the relative uptake, time trends or factors influencing uptake in those at increased breast cancer risk not known to be carriers. The aim of this study is to assess these factors in both groups. Methods: BRRM uptake was assessed from entry to the Manchester Family History Clinic or from date of personal BRCA1/2 test. Follow up was censored at BRRM, breast cancer diagnosis, death or January 01, 2020. Cumulative incidence and cause specific and competing risk regression analyses were used to assess the significance of factors associated with BRRM. Results: Of 7195 women at ≥25% lifetime breast cancer risk followed for up to 32 years, 451 (6.2%) underwent pre-symptomatic BRRM. Of those eligible in different risk groups the 20-year uptake of BRRM was 47.7%-(95%CI = 42.4–53.2%) in 479 BRCA1/2 carriers; 9.0% (95%CI = 7.26–11.24%) in 1261 women at ≥40% lifetime risk (non-BRCA), 4.8%-(95%CI = 3.98–5.73%) in 3561 women at 30–39% risk and 2.9%-(95%CI = 2.09–4.09%) in 1783 women at 25–29% lifetime risk. In cause-specific Cox regression analysis death of a sister with breast cancer<50 (OR = 2.4; 95%CI = 1.7–3.4), mother<60 (OR = 1.9; 95%CI = 1.5–2.3), having children (OR = 1.4; 95%CI = 1.1–1.8), breast biopsy (OR = 1.4; 95%CI = 1.0–1.8) were all independently associated with BRRM uptake, while being older at assessment was less likely to be associated with BRRM (>50; OR = 0.26, 95%CI = 0.17–0.41). Uptake continued to rise to 20 years from initial risk assessment. Conclusion: We have identified several additional factors that correlate with BRRM uptake and demonstrate continued increases over time. These factors will help to tailor counselling and support for women. Highlights: BRRM continues even 20 years post original breast cancer risk assessment. Potential triggers include death of mother/sister, children and a breast biopsy. Uptake is clearly informed by lifetime risk of BC and higher in younger the women.